Factors that influence online purchase intention among UUM postgraduate students - Khairull Anuar, Ismail (2017)
Online market is one of the industry that are currently developing and have many potential to become one of the best market in the world. Many entrepreneur have start to move from plain brick and mortar business to adopt both physical and online shops to set up their business and attract customers. There are also some entrepreneur that only focus on online commerce and only set up online shops to perform their business. Advancement in delivery services that now provided more services and allowed for a heavier and bigger products have made online business more convenience to perform by the entrepreneur and sought after by the consumer. Students are one of the prospects customers that have interest and skills to patronage and use online shopping. This study aim to identify and examine the factors that influence online purchase intentions among postgraduate students. Seven dimensions were used in this study consisting of product, price, promotion, product risk, delivery risk, privacy risk and financial risk. This study was conducted in UUM and 500 questionnaires were distributed and 394 of them were recovered and valid to be used as the sample for the study while 50 were lost and 56 were damaged and excluded from the study. This study reveals that the highest dimensions to affect online purchase intentions are products. Meanwhile delivery and financial risk dimensions are revealed to have no significant relationship with online purchase intentions.